2009
DOI: 10.1103/physrevlett.103.263901
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Magnetic Field Enhancement with Metallic Nanowire: Role of Surface Impedance in Babinet’s Principle for Sub-Skin-Depth Regime

Abstract: We propose and analyze the "complementary" structure of a metallic nanogap, namely, the metallic nanowire for magnetic field enhancement. A huge enhancement of the field up to a factor of 300 was achieved. Introducing the surface impedance concept, we also develop and numerically confirm a new analytic theory which successfully predicts the field enhancement factors for metal nanostructures. Compared to the predictions of the classical Babinet principle applied to a nanogap, an order of magnitude difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…When the nanogaps are irradiated with THz waves, induced current charges the capacitor formed by the sidewalls of the nanogap. For smaller gaps, Coulomb attraction brings opposite charges closer to the sidewalls and generates a field enhancement that is inversely proportional to the gap size 11,24 . Previously, a field enhancement of 1,000 was experimentally demonstrated for a non-resonant 70-nm-wide slit 11 , and much larger enhancements are expected for 1-nm-wide gaps.…”
Section: Article Nature Communications | Doi: 101038/ncomms3361mentioning
confidence: 99%
“…When the nanogaps are irradiated with THz waves, induced current charges the capacitor formed by the sidewalls of the nanogap. For smaller gaps, Coulomb attraction brings opposite charges closer to the sidewalls and generates a field enhancement that is inversely proportional to the gap size 11,24 . Previously, a field enhancement of 1,000 was experimentally demonstrated for a non-resonant 70-nm-wide slit 11 , and much larger enhancements are expected for 1-nm-wide gaps.…”
Section: Article Nature Communications | Doi: 101038/ncomms3361mentioning
confidence: 99%
“…2,3 Even in lower frequencies where most metals are considered as perfect electric conductor ͑PEC͒, it has theoretically 4 and experimentally 5,6 been demonstrated that enhanced transmissions of electromagnetic wave through slits or rectangular apertures are possible when the thickness and the width of apertures are both in extreme subwavelength regime. As the metal thickness is reduced below submicron, apertures, and other fundamental metallic compositions for metamaterials, such as nanowires, 7,8 nanoparticles, 9 and split ring resonators, 10 cannot any more exist in free space. They must necessarily be fabricated on rigid substrates.…”
mentioning
confidence: 99%
“…According to Ref. [18] we shall consider the complimentary structures: metallic nanogap and metallic nanowire of the same sizes illuminated by the TM and TE waves, respectively. Electric field enhancement for the nanogap has been discussed above and can be estimated in terms of the electric field at the center of the …”
Section: Resultsmentioning
confidence: 99%